2013
DOI: 10.1103/physrevb.88.165403
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium spin-current detection with a single Kondo impurity

Abstract: We present a theoretical study based on the Anderson model of the transport properties of a Kondo impurity (atom or quantum dot) connected to ferromagnetic leads, which can sustain a nonequilibrium spin current. We analyze the case where the spin current is injected by an external source and when it is generated by the voltage bias. Due to the presence of ferromagnetic contacts, a static exchange field is produced that eventually destroys the Kondo correlations. We find that such a field can be compensated by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
(90 reference statements)
1
17
0
Order By: Relevance
“…One of the broadly used EOM techniques [6,7,10,11,16] is the decoupling scheme proposed by Lacroix [17]. This scheme was based on the Heisenberg equations of motion with differentiation over one time variable.…”
Section: Introductionmentioning
confidence: 99%
“…One of the broadly used EOM techniques [6,7,10,11,16] is the decoupling scheme proposed by Lacroix [17]. This scheme was based on the Heisenberg equations of motion with differentiation over one time variable.…”
Section: Introductionmentioning
confidence: 99%
“…If the leads are magnetic, the Kondo resonance is perturbed by the exchange interaction in the leads [9], splitting the zero-bias anomaly in the differential conductance in both collinear [10] and noncollinear [11] orientations of the leads. It was, furthermore, theoretically shown that spin accumulation associated with a spin-dependent bias also splits the Kondo resonance, which manifests in the charge and spin current [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…By treating the lead electrons as a mean field, to lowest order in , the magnetic lead γ splits the energy degeneracy on the dot by [13] …”
mentioning
confidence: 99%
“…In the present work, we study the nonequilibrium Kondo effect and the transport properties in a QD coupled to graphene-based leads by solving the pseudogap Anderson model [36][37][38][39][40][41][42][43][44][45] with the equation of motion (EOM) technique [46][47][48]. In our studies, a magnetic field is applied to the QD causing a Kondo resonance splitting, and a finite on-site Coulomb interaction (U ) is considered resulting in a shift of the main QD energy level.…”
Section: Introductionmentioning
confidence: 99%